Measuring the outcome of contact tracing. 2. The responsibilities of the health worker and the outcome of contact investigations. Issue 3 (June 1978) - Mills, A; Satin, A
Abstract : The previous paper (Satin and Mills, 1978) concerned information on patients who were interviewed by health workers in five selected clinics; information on the contacts named by these patients was similarly analysed. This paper describes and evaluates the activities of the health workers and the outcome of contact investigations. At all stages of the contact tracing process, differences were observed between men and women. It was found that more than half of the male contacts and half the female contacts were known to have been examined. Of those contacts examined, at least two-thirds of them attended the same clinic as the patient who had named them, and 85% of these contacts were found to have a treatable condition. It will be seen that the concept of success or effectiveness of contact tracing is complex in definition and measurement.